2002
DOI: 10.1046/j.1526-4610.2002.02125.x
|View full text |Cite
|
Sign up to set email alerts
|

Amitriptyline Versus Amitriptyline Combined With Fluoxetine in the Preventative Treatment of Transformed Migraine: A Double‐Blind Study

Abstract: We were unable to demonstrate any significant benefit from amitriptyline plus fluoxetine over amitriptyline alone in the treatment of chronic daily headache/transformed migraine. Because of the small number of subjects involved and the short duration of our study, a type II error cannot be excluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 19 publications
0
66
0
Order By: Relevance
“…A doubleblind placebo-controlled study showed fluoxetine to be useful in the treatment of chronic daily head a c h e 1 1 . Others, using it in association with amitriptyline, could not observe this effect 12 . The objective of this study was to test the eff icacy of fluoxetine prophylaxis in a group of child ren and adolescents with primary CDH thro u g h a prospective, randomized, double blind, placebo-controlled, crossover study.…”
mentioning
confidence: 95%
“…A doubleblind placebo-controlled study showed fluoxetine to be useful in the treatment of chronic daily head a c h e 1 1 . Others, using it in association with amitriptyline, could not observe this effect 12 . The objective of this study was to test the eff icacy of fluoxetine prophylaxis in a group of child ren and adolescents with primary CDH thro u g h a prospective, randomized, double blind, placebo-controlled, crossover study.…”
mentioning
confidence: 95%
“…12 Evidence-based prophylactic medications for episodic migraine are often used for chronic migraine. These agents include topiramate, 13,14 gabapentin, 15 tizanidine, 16 fluoxetine, 17 amitriptyline, 18 and valproate. 19,20 It is important to note that of these agents commonly used for treating episodic migraine, only topiramate has been shown to be efficacious in randomized, placebo-controlled clinical trials in patients with chronic migraine.…”
Section: Treatment Plan For Chronic Migrainementioning
confidence: 99%
“…15 One randomized open study in 49 subjects with CM compared sodium valproate 750 mg/day to topiramate 75 mg/day. 16 Three months after randomization, significant reduction in 30-day headache days with respect to baseline ( p Ͻ 0.00001) and significant reduction in Migraine Disability Assessment (MIDAS) scores ( p Ͻ 0.00001) were recorded in both groups.…”
Section: Treatment Options For Chronic Migrainementioning
confidence: 99%